Development of Guidelines for Enhancing Code of Ethics of Teaching Profession Within Pre-service Teachers of Faculty of Education, Phuket Rajabhat University - Sadjarak, Somkiat (Journal of Graduate Research, 2023)
The purposes of this study were to: 1) develop guidelines for enhancing the code of ethics of the teaching profession, 2) evaluate the guidelines for enhancing the code of the ethics of teaching profession, and 3) assess the practices of the code of ethics of teaching profession within pre-service teachers studying at the Faculty of Education, Phuket Rajabhat University. The target groups consisted of 50 supervising teachers, 19 school administrators, 20 university supervisors, and 38 school teachers from 19 target schools where the 5th-year students from the Faculty of Education practiced teaching professional experience during the academic year 2022. The target groups were selected by purposive sampling. Research instruments included 1) an evaluation form to evaluate the practices of the code of ethics of teaching profession within pre-service teachers, and 2) a series of questions for group discussions. The statistical analysis used comprised of mean ( ), standard deviation (S.D.), content analysis was used to analyze the qualitative data, and data validation through triangulation. The results revealed that; 1) the guidelines for enhancing the code of ethics of teaching profession within the pre-service teachers consisted of five steps: (1) study basic information, (2) collaborating with several departments, (3) organizing various activities, (4) integrating activities, and (5) maintaining continuous coordination between departments; 2) Expert evaluations reported that the guidelines for enhancing the code of ethics of teaching profession within the pre-service teachers were generally appropriate for high level; and 3) the results from assessing pre-service teachers’ practices of the code of ethics for teaching profession have pointed out that those pre-service teachers demonstrated behavior aligned with five dimensions of the code of ethic at a high level overall.